AVALIAÇÃO DA COR E PERDA DE ÁGUA DA CARNE DE FRANGO REVESTIDA COM FILME BIODEGRADÁVEL À BASE DE PECTINA - SILVINO, Breno Correa Maciel; GOMES, Ana Carolina Alves; SANTOS, Aylpy Renan Dutra; DALEGRAVE, Caroline de Brito; DORNAS, Isabeli Mantovani; OLIVEIRA, Dalton Mendes de (ANAIS DO ENIC, 2026)
.